Moral Education of Junior Teenagers in the Process of Socially Significant Activity - G I Vedeneyevа (Peoples' Friendship University of Russia (RUDN University), 2011)
The analysis of the interrelation of the revealed moral conceptions, notions and vital values of junior teenagers with their participating in the life of their class, their local area is submitted.